Antenatal exposure to fenoterol is not associated with the development of retinopathy of prematurity in infants born before 32 weeks of gestation - Hudalla, Hannes; Bruckner, Thomas; Pöschl, Johannes; Strowitzki, Thomas; Kuon, Ruben-Jeremias (Archives of gynecology and obstetrics, 2020)
Despite safety concerns, β2-sympathomimetics are still widely used as tocolytic agents. β-Blockers in turn are used to treat vasculo-proliferative diseases of the newborn such as retinopathy of prematurity (ROP), which may lead to visual impairment and blindness. The scope of this study was to investigate whether antenatal exposure to the β2-sympathomimetic fenoterol contributes to the development of ROP.